Rho GDP-Dissociation Inhibitor 2 Inhibits C-X-C Chemokine Receptor Type 4-Mediated Acute Lymphoblastic Leukemia Cell Migration - Luo, Jixian; Wang, Junting; Zheng, Huiguang; Wang, Lan (Frontiers in Oncology, 2020)
Although we currently have a good understanding of the role C-X-C chemokine receptor type 4 (CXCR4) in T cell acute lymphoblastic leukemia (T-ALL), the mechanism of CXCR4-mediated T-ALL migration remain elusive. Therefore we focused on the downstream signals of CXCR4 that contribute to T-ALL cell migration in this study. Rho GDP-dissociation inhibitor 2 (RhoGDI2) is expressed preferentially in lymphocytes. It interacts with and regulates the activation of Rho proteins by inhibiting the dissociation of GDP and t he binding of GTP. In the previous study, we have demonstrated that RhoA and RhoC are activated and required for CXCR4-mediated JURKAT cell migration. In the present work we investigated the role of RhoGDI2 in CXCR4-mediated T-ALL cell migration. Results showed that RhoGDI2 sh2 significantly released its inhibition effects on T-ALL cell migration towards CXCL12 (C-X-C motif chemokine ligand 12). Phosphorylation of RhoGDI2 on Y24 and Y153 released RhoA and RhoC from RhoGDI2, which recovered CXCR4-mediated migration towards CXCL12, although the phosphorylation of Y130 has less effect on RhoA or RhoC binding. Furthermore, Src was activated by CXCL12. Transfection of siRNAs to Src reduced CXCR4-mediated migration. Src was required for the phosphorylation of RhoGDI2 on Y153, while ABL1 was activated by CXCL12 and responsible for the phosphorylation of RhoGDI2 on Y24 and Y130. Similarly, knockdown of the expression of ABL1 by siRNAs reduced the CXCR4-mediated migration. Therefore, RhoGDI2 may be a brake for CXCR4-positive T-ALL migration. Since migration is a prerequisite for infiltration of leukemia, this work may suggest the possible involvement of RhoGDI2 in infiltration of T-ALL.